Preparation method of surface modified hard carbon sodium ion battery negative electrode material
Through the preparation method of surface modified hard carbon materials, the problem of insufficient performance of hard carbon materials in sodium ion batteries is solved, the safety and rate performance are improved, the cost is reduced, and it is suitable for industrial production.
Patent Information
- Application Number
- CN202411294851.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-14
AI Technical Summary
Hard carbon materials have poor rate performance and cycling performance in sodium ion batteries, which are prone to polarization to form sodium dendrites, resulting in safety hazards. The existing process costs are high, making it difficult to achieve large-scale industrial production.
Prepare surface-modified hard carbon materials through low-temperature carbonization, refinement, sand-mill modification and high-temperature carbonization, increase oxygen-containing functional groups such as -OH and -COOH on the surface of the material, improve the wetting and circulation stability of the electrolyte, and avoid sodium Dentite formation, optimize electrochemical properties.
It significantly improves the safety, rate performance and cycle stability of sodium ion batteries, reduces production costs, and is suitable for large-scale industrial production.
Smart Images

Figure CN119176541A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a surface-modified hard carbon sodium ion battery negative electrode material. Background Art
[0002] With the rapid development of renewable energy technology, the world's energy structure is shifting from traditional fossil energy to renewable energy. The efficient use of renewable energy requires supporting energy storage facilities to ensure the continuity and stability of power supply.
[0003] Among many energy storage technologies, sodium-ion batteries are considered to be an ideal choice for future large-scale energy storage due to their abundant resources, low cost, and high safety. As an important component of sodium-ion batteries, hard carbon anode materials play a decisive role in their electrochemical performance.
[0004] However, hard carbon materials have poor rate and cycle performance. During the charging process, sodium dendrites are easily formed on the surface due to polarization, which can pierce the separator and cause serious safety hazards. Exploring hard carbon negative electrodes with excellent cycle, rate and safety performance is the key to the industrialization of sodium-ion batteries. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a surface modified hard carbon sodium ion battery negative electrode material, which has the characteristics of high safety, excellent rate performance, high cycle stability and strong process feasibility.
[0006] The present invention can be implemented by the following technical solutions: The present invention discloses a method for preparing a surface-modified hard carbon sodium ion battery negative electrode material, comprising the following steps: S1. Preparation of precursor: crushing and sieving the hard carbon raw material to obtain precursor powder; S2, low temperature carbonization: the precursor powder obtained in step S1 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material; S3, crushing and refining: crushing the low-temperature carbonized material obtained in step S2 to obtain refined low-temperature carbonized material; S4, sand grinding modification: wet sand grinding the refined low-temperature carbonized material obtained in step S3 with a modifier to obtain a surface-modified low-temperature carbonized slurry; S5, drying treatment: centrifuging, washing and drying the surface-modified low-temperature carbonized slurry obtained in step S4 to obtain a surface-modified low-temperature carbonized material; S6, high temperature carbonization: the surface-modified low-temperature carbonized material obtained in step S5 is subjected to high temperature carbonization under a protective atmosphere to obtain a surface-modified hard carbon material.
[0007] Furthermore, in step S2, the conditions for low-temperature calcination are: heating rate of 2-15 ℃ / min, pretreatment temperature of 300-800 ℃, pretreatment time of 1-5 h; protective atmosphere is nitrogen and / or argon. In step S2, the conditions for low-temperature carbonization will affect the effect of the present invention. If the heating rate is slow, the treatment temperature is high, and the treatment time is long, the carbonization degree of the low-temperature carbonized material is high; otherwise, the carbonization degree of the low-temperature carbonized material is low. If the carbonization degree is too low, the hard carbon raw material is not completely carbonized, and the volatile matter is too high, it is not conducive to the subsequent sand grinding to fine particle size; if the carbonization degree is too high, the volatile matter of the carbonized material is too low, the reaction activity is low, and it is not conducive to surface oxidation modification during the sand grinding process.
[0008] Furthermore, in step S3, the particle size of the refined low-temperature carbonized material is controlled to be: 10 μm ≤ D50 ≤ 200 μm. If D50 is too large, the equipment will be blocked in the subsequent sanding process, affecting the normal operation of the equipment; if D50 is too small, the energy consumption of the process will be too high, the output will be low, which is not conducive to actual production cost control.
[0009] Further, in step S4, the modifier is an oxidant, and the oxidant is one or more of nitric acid and its salts, perchloric acid and its salts, dichromic acid and its salts, permanganic acid and its salts, persulfate and its salts, sulfuric acid and its salts. The surface of the carbonized material undergoes oxidation modification under the action of the oxidant, and active groups such as -OH and -COOH are grafted onto the surface. On the one hand, the temperature is controlled, and on the other hand, the collision, friction and shearing between the sand milling medium and the solid particle material increase the surface defects of the solid particles and enhance the reaction activity of the material surface. Multiple effects synergistically promote the occurrence of oxidation reaction, thereby achieving the purpose of surface modification.
[0010] Furthermore, in step S4, the amount of modifier added is 0.1-5% of the mass of the refined low-temperature carbonized material, and the solid content is 10-50%. Among them, the amount of modifier added will affect the effect of the present invention. If the amount of modifier added is too low, the effect of surface oxidation cannot be achieved; if the amount of modifier used is too high, the surface of the carbon material is over-oxidized, the carbon layer is etched, and the specific surface area increases, which has an adverse effect on battery performance. Among them, if the solid content is too high, the viscosity of the slurry is too high, the fluidity is poor, and the grinding efficiency is affected; if the solid content is too low, the processing amount of each batch of carbon material is too low, which increases the production cost.
[0011] Furthermore, in step S4, the particle size of the sand milling process is controlled to be sand milled until the material D50 is 3-8 μm. During the sand milling process, the sand milling medium generates shear crushing force and extrusion crushing force on the low-temperature carbonized material, so that the material particles are further crushed to form small particles, thereby achieving the purpose of further crushing the material particle size. Compared with other crushing methods commonly used in the hard carbon preparation process (mechanical grinding and air flow powder, etc.), the sand milling process uses sand milling beads as a crushing medium, and makes full use of the collision, friction and shearing effects between the sand milling medium and the solid particle material to achieve the purpose of quickly reducing the particle size of the solid particles. It has the advantages of low energy consumption and high efficiency, which is beneficial to reducing production costs. Therefore, the present invention uses step S3 as coarse grinding and step S4 as fine grinding to fully reduce production energy consumption on the basis of ensuring the product particle size.
[0012] Furthermore, in step S4, the temperature of the sand milling process is controlled at 30-80°C. During the sand milling process, the temperature of the heat-generating slurry will gradually rise due to grinding, and cooling water is required to control the temperature of the sand mill at an appropriate value. On the one hand, if the sand milling temperature is too low, it is not conducive to the occurrence of the oxidation reaction; if the temperature is too high and exceeds the maintenance temperature, it will affect the service life of the equipment.
[0013] Further, in step S6, the conditions for high temperature carbonization are: heating rate of 0.5-10°C / min, carbonization temperature of 900-1600°C, and carbonization time of 2-10 h.
[0014] Furthermore, in step S1, the hard carbon raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, and sub-bituminous coal; and the sieve aperture is ≤2 cm.
[0015] Furthermore, in step S3, the pulverizing method is one or more of roller milling, mechanical milling, air flow milling, dry ball milling, and Raymond milling.
[0016] In step S5, unreacted oxidant and residues after the reaction are removed by centrifugation and water washing to avoid introducing impurities into the hard carbon material and affecting the battery performance.
[0017] In the present invention, the hard carbon material is modified with oxygen-containing functional groups such as -OH and -COOH, thereby achieving the improvement of the electrochemical performance of the hard carbon negative electrode. On the one hand, the surface polarity of the modified hard carbon is enhanced, the wettability with the electrolyte is increased, and the electrolyte fully penetrates into the pores of the material, thereby increasing the diffusion coefficient of sodium ions at the interface and improving the charge and discharge rate performance; on the other hand, the oxygen-containing functional groups on the surface of the hard carbon material interact with the electrolyte, promoting the decomposition of the electrolyte to construct a thinner and more stable SEI, and improving the cycle stability of the hard carbon material.
[0018] The present invention provides a method for preparing a surface-modified hard carbon sodium ion battery negative electrode material, which has the following beneficial effects: First, good safety. The hard carbon material is modified with oxygen-containing functional groups such as -OH and -COOH. The surface polarity of the modified hard carbon is enhanced, which increases the wettability with the electrolyte, allowing the electrolyte to fully penetrate into the pores of the material, thereby increasing the diffusion coefficient of sodium ions at the interface, avoiding the formation of sodium dendrites during charging, and thus improving the safety performance of the battery; Second, the rate performance is excellent. The hard carbon surface modification layer increases the wettability with the electrolyte, improves the diffusion coefficient of sodium ions at the interface, and thus improves the rate performance of the material; Third, the cycle stability is high. The present invention not only avoids the capacity loss of the hard carbon material due to sodium precipitation during the charging process, but also promotes the decomposition of the electrolyte to build a thinner and more stable SEI through the oxygen-containing functional groups on the surface of the hard carbon material, thereby improving the cycle stability of the hard carbon material. Fourth, the process is highly feasible. The core process of the present invention is an industrial sand grinding process. Compared with the pulverization methods such as air flow powder commonly used in current industrial production, sand grinding has lower energy consumption and is more suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The following are the cycle test curves of Application Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0021] The present invention discloses a method for preparing a surface-modified hard carbon sodium ion battery negative electrode material, comprising the following steps: S1. Preparation of precursor: crushing and sieving the hard carbon raw material to obtain precursor powder; S2, low temperature carbonization: the precursor powder obtained in step S1 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material; S3, crushing and refining: crushing the low-temperature carbonized material obtained in step S2 to obtain refined low-temperature carbonized material; S4, sand grinding modification: wet sand grinding the refined low-temperature carbonized material obtained in step S3 with a modifier to obtain a surface-modified low-temperature carbonized slurry; S5, drying treatment: centrifuging, washing and drying the surface-modified low-temperature carbonized slurry obtained in step S4 to obtain a surface-modified low-temperature carbonized material; S6, high temperature carbonization: the surface-modified low-temperature carbonized material obtained in step S5 is subjected to high temperature carbonization under a protective atmosphere to obtain a surface-modified hard carbon material.
[0022] Furthermore, in step S3, the particle size of the refined low-temperature carbonized material is controlled to be: 10 μm≤ D50≤ 200 μm.
[0023] Furthermore, in step S4, the modifier is an oxidant, and the oxidant is one or more of nitric acid and its salts, perchloric acid and its salts, dichromic acid and its salts, permanganic acid and its salts, persulfate and its salts, and sulfuric acid and its salts.
[0024] Furthermore, in step S4, the amount of the modifier added is 0.1-5% of the mass of the refined low-temperature carbonized material, and the solid content is 10-50%.
[0025] Further, in step S4, the particle size of the sanding process is controlled to be sanded until the material D50 is 3-8 μm.
[0026] Further, in step S4, the temperature of the sanding process is controlled to be 30-80°C.
[0027] Furthermore, in step S2, the conditions for low-temperature calcination are: a heating rate of 2-15°C / min, a pretreatment temperature of 300-800°C, a pretreatment time of 1-5 h; and a protective atmosphere of nitrogen and / or argon.
[0028] Further, in step S6, the conditions for high temperature carbonization are: heating rate of 0.5-10°C / min, carbonization temperature of 900-1600°C, and carbonization time of 2-10 h.
[0029] Furthermore, in step S1, the hard carbon raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, and sub-bituminous coal; and the sieve aperture is ≤2 cm.
[0030] Furthermore, in step S3, the pulverizing method is one or more of roller milling, mechanical milling, air flow milling, dry ball milling, and Raymond milling.
[0031] Example 1 This embodiment relates to a surface-modified sodium ion battery hard carbon negative electrode material, and the preparation method thereof comprises the following steps: S1. Preparation of precursor: crushing the hard carbon raw material, sieving, and obtaining precursor powder. Specifically, the hard carbon raw material is walnut shells or nut shells, and the sieve mesh size is ≤2 cm.
[0032] S2, low temperature carbonization: the precursor powder obtained in step S1 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material. Specifically, the conditions for low temperature calcination are: a heating rate of 15°C / min, a pretreatment temperature of 600°C, a pretreatment time of 1h, and a protective atmosphere of nitrogen.
[0033] S3, crushing and refining: crushing the low temperature carbonized material obtained in step S2 to obtain refined low temperature carbonized material. Specifically, the particle size of the refined low temperature carbonized material is controlled to be: 10 μm ≤ D50 ≤ 200 μm. Optionally, the crushing method is a double roller or mechanical grinding.
[0034] S4, sanding modification: wet sanding the refined low-temperature carbonized material obtained in step S3 with the modifier to obtain a surface-modified low-temperature carbonized slurry. Specifically, the particle size of the sanding process is controlled to be sanded to a material D50 of 3-8 μm. Optionally, the modifier is an oxidant, and the oxidant is nitric acid and its salts; the amount of the modifier added is 5% of the mass of the refined low-temperature carbonized material, and the solid content is controlled at 10-50%; the temperature of the sanding process is controlled at 60°C.
[0035] S5, drying treatment: centrifuging, washing and drying the surface-modified low-temperature carbonized slurry obtained in step S4 to obtain a surface-modified low-temperature carbonized material.
[0036] S6, high temperature carbonization: the surface-modified low temperature carbonized material obtained in step S5 is subjected to high temperature carbonization under a protective atmosphere to obtain a surface-modified hard carbon material. Specifically, the conditions for high temperature carbonization are: a heating rate of 10°C / min, a carbonization temperature of 1300°C, and a carbonization time of 2 hours.
[0037] Example 2 This embodiment relates to a surface-modified sodium ion battery hard carbon negative electrode material, and the preparation method thereof comprises the following steps: S1. Preparation of precursor: crushing and sieving hard carbon raw materials to obtain precursor powder. Specifically, the hard carbon raw materials are fir, oak, anthracite, lignite, sub-bituminous coal, and the sieve aperture is ≤2 cm.
[0038] S2, low temperature carbonization: the precursor powder obtained in step S1 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material. Specifically, the conditions for low temperature calcination are: a heating rate of 8 °C / min, a pretreatment temperature of 300 °C, a pretreatment time of 5 h, and an argon protective atmosphere.
[0039] S3, crushing and refining: crushing the low temperature carbonized material obtained in step S2 to obtain refined low temperature carbonized material. Specifically, the particle size of the refined low temperature carbonized material is controlled to be: 10 μm≤ D50≤ 200 μm. Optionally, the crushing method is dry ball milling or Raymond milling.
[0040] S4, sanding modification: wet sanding the refined low-temperature carbonized material obtained in step S3 with the modifier to obtain a surface-modified low-temperature carbonized slurry. Specifically, the particle size of the sanding process is controlled to be sanded to a material D50 of 3-8 μm. Optionally, the modifier is an oxidant, and the oxidant is perchloric acid and its salts; the amount of the modifier added is 3% of the mass of the refined low-temperature carbonized material, and the solid content is controlled at 10-50%; the temperature of the sanding process is controlled at 40°C.
[0041] S5, drying treatment: centrifuging, washing and drying the surface-modified low-temperature carbonized slurry obtained in step S4 to obtain a surface-modified low-temperature carbonized material.
[0042] S6, high temperature carbonization: the surface-modified low temperature carbonized material obtained in step S5 is subjected to high temperature carbonization under a protective atmosphere to obtain a surface-modified hard carbon material. Specifically, the conditions for high temperature carbonization are: a heating rate of 5°C / min, a carbonization temperature of 900°C, and a carbonization time of 10 h.
[0043] Example 3 This embodiment relates to a surface-modified sodium ion battery hard carbon negative electrode material, and the preparation method thereof comprises the following steps: S1. Preparation of precursor: crushing and sieving hard carbon raw materials to obtain precursor powder. Specifically, the hard carbon raw materials are walnut shells, nut shells, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, and the sieve aperture is ≤2 cm.
[0044] S2, low temperature carbonization: the precursor powder obtained in step S1 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material. Specifically, the conditions for low temperature calcination are: a heating rate of 2°C / min, a pretreatment temperature of 800°C, a pretreatment time of 3h; and the protective atmosphere is nitrogen and argon.
[0045] S3, crushing and refining: crushing the low temperature carbonized material obtained in step S2 to obtain refined low temperature carbonized material. Specifically, the particle size of the refined low temperature carbonized material is controlled to be: 10 μm≤ D50≤ 200 μm. Optionally, the crushing method is double roller or dry ball milling.
[0046] S4, sanding modification: wet sanding the refined low-temperature carbonized material obtained in step S3 with the modifier to obtain a surface-modified low-temperature carbonized slurry. Specifically, the particle size of the sanding process is controlled to be sanded to a material D50 of 3-8 μm. Optionally, the modifier is an oxidant, and the oxidant is a dichromatic acid and its salt; the amount of the modifier added is 0.5% of the mass of the refined low-temperature carbonized material, and the solid content is controlled at 10-50%; the temperature of the sanding process is controlled at 80°C.
[0047] S5, drying treatment: centrifuging, washing and drying the surface-modified low-temperature carbonized slurry obtained in step S4 to obtain a surface-modified low-temperature carbonized material.
[0048] S6, high temperature carbonization: the surface-modified low temperature carbonized material obtained in step S5 is subjected to high temperature carbonization under a protective atmosphere to obtain a surface-modified hard carbon material. Specifically, the conditions for high temperature carbonization are: a heating rate of 0.5°C / min, a carbonization temperature of 1600°C, and a carbonization time of 6 hours.
[0049] Example 4 This embodiment relates to a surface-modified sodium ion battery hard carbon negative electrode material, and the preparation method thereof comprises the following steps: S1. Preparation of precursor: crushing and sieving hard carbon raw materials to obtain precursor powder. Specifically, the hard carbon raw materials are walnut shells, nut shells, apricot shells, straw, reeds, and sub-bituminous coal, and the sieve aperture is ≤2 cm.
[0050] S2, low temperature carbonization: the precursor powder obtained in step S1 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material. Specifically, the conditions for low temperature calcination are: a heating rate of 5 °C / min, a pretreatment temperature of 400 °C, a pretreatment time of 3 h; and the protective atmosphere is nitrogen and argon.
[0051] S3, crushing and refining: crushing the low temperature carbonized material obtained in step S2 to obtain refined low temperature carbonized material. Specifically, the particle size of the refined low temperature carbonized material is controlled to be: 10 μm ≤ D50 ≤ 200 μm. Optionally, the crushing method is mechanical grinding.
[0052] S4, sanding modification: wet sanding the refined low-temperature carbonized material obtained in step S3 with the modifier to obtain a surface-modified low-temperature carbonized slurry. Specifically, the particle size of the sanding process is controlled to be sanded to a material D50 of 3-8 μm. Optionally, the modifier is an oxidant, and the oxidant is nitric acid and its salts, permanganate and its salts, persulfate and its salts, sulfuric acid and its salts; the amount of the modifier added is 2% of the mass of the refined low-temperature carbonized material, and the solid content is controlled at 10-50%; the temperature of the sanding process is controlled at 50°C.
[0053] S5, drying treatment: centrifuging, washing and drying the surface-modified low-temperature carbonized slurry obtained in step S4 to obtain a surface-modified low-temperature carbonized material.
[0054] S6, high temperature carbonization: the surface-modified low temperature carbonized material obtained in step S5 is subjected to high temperature carbonization under a protective atmosphere to obtain a surface-modified hard carbon material. Specifically, the conditions for high temperature carbonization are: a heating rate of 3°C / min, a carbonization temperature of 1200°C, and a carbonization time of 3 hours.
[0055] Example 5 This embodiment relates to a surface-modified sodium ion battery hard carbon negative electrode material, and the preparation method thereof comprises the following steps: S1. Preparation of precursor: crushing and sieving hard carbon raw materials to obtain precursor powder. Specifically, the hard carbon raw materials are walnut shells, nut shells, apricot shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, and the sieve aperture is ≤2 cm.
[0056] S2, low temperature carbonization: the precursor powder obtained in step S1 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material. Specifically, the conditions for low temperature calcination are: a heating rate of 13°C / min, a pretreatment temperature of 400°C, a pretreatment time of 4 h; and the protective atmosphere is nitrogen and argon.
[0057] S3, crushing and refining: crushing the low temperature carbonized material obtained in step S2 to obtain refined low temperature carbonized material. Specifically, the particle size of the refined low temperature carbonized material is controlled to be: 10 μm≤ D50≤ 200 μm. Optionally, the crushing method is air flow powder or dry ball milling.
[0058] S4, sanding modification: wet sanding the refined low-temperature carbonized material obtained in step S3 with the modifier to obtain a surface-modified low-temperature carbonized slurry. Specifically, the particle size of the sanding process is controlled to sanding until the material D50 is 3-8μm. Optionally, the modifier is an oxidant, and the oxidant is nitric acid and its salts, perchloric acid and its salts, dichromic acid and its salts, permanganic acid and its salts, persulfate and its salts, sulfuric acid and its salts; the amount of the modifier added is 4% of the mass of the refined low-temperature carbonized material, and the solid content is 10-50%; the temperature of the sanding process is controlled to 70°C.
[0059] S5, drying treatment: centrifuging, washing and drying the surface-modified low-temperature carbonized slurry obtained in step S4 to obtain a surface-modified low-temperature carbonized material.
[0060] S6, high temperature carbonization: the surface-modified low temperature carbonized material obtained in step S5 is subjected to high temperature carbonization under a protective atmosphere to obtain a surface-modified hard carbon material. Specifically, the conditions for high temperature carbonization are: a heating rate of 5°C / min, a carbonization temperature of 1400°C, and a carbonization time of 3 hours.
[0061] Application Example 1 This embodiment relates to a surface-modified sodium ion battery hard carbon negative electrode material, and the preparation method thereof comprises the following steps: S1. Preparation of precursor: crush the coconut shell raw material, sieve it, and the sieve mesh size is 2 cm to obtain the precursor powder; S2, low temperature carbonization: the precursor powder obtained in step S1 is subjected to low temperature carbonization under nitrogen protection, wherein the heating rate is 5 °C / min, the treatment temperature is 600 °C, and the pretreatment time is 2 h. A low temperature carbonized material is obtained; S3, crushing and refining: crushing the low-temperature carbonized material obtained in step S2 to D50≤50μm by ball milling to obtain refined low-temperature carbonized material; S4, sand grinding modification: the refined low temperature carbonized material obtained in step S3, H 2 O 2 and deionized water, where H 2 O 2 The addition amount is 1% of the carbonized material, the solid content of the slurry is 25%, and the material is sand-ground to D50 = 7μm at a temperature of 50°C to obtain a surface-modified low-temperature carbonized slurry; S5, drying treatment: centrifuging, washing and drying the surface-modified low-temperature carbonized slurry obtained in step S4 to obtain a surface-modified low-temperature carbonized material; S6. High-temperature carbonization: The surface-modified low-temperature carbonized material obtained in step S5 is subjected to high-temperature carbonization under nitrogen gas protection, with a heating rate of 5°C / min, a carbonization temperature of 1400°C, and a carbonization time of 3h to obtain a surface-modified hard carbon material.
[0062] The electrochemical performance of the obtained material was tested according to the following method: the hard carbon material, Super P, CMC, and SBR of Application Example 1 were mixed into a slurry in a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on a copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, with metallic sodium as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2032 type button cell in a glove box. The above button cell was subjected to a constant current charge and discharge test, with a current density of 0.1C (1C-300 mAh / g) and a voltage range of 2-0.005V.
[0063] Application Example 2 This embodiment relates to a surface-modified sodium ion battery hard carbon negative electrode material, and the preparation method thereof comprises the following steps: S1. Preparation of precursor: crush the coconut shell raw material, sieve it, and the sieve mesh size is 2 cm to obtain the precursor powder; S2, low temperature carbonization: the precursor powder obtained in step S1 is subjected to low temperature carbonization under nitrogen protection, wherein the heating rate is 5 °C / min, the treatment temperature is 600 °C, and the pretreatment time is 2 h. A low temperature carbonized material is obtained; S3, crushing and refining: crushing the low-temperature carbonized material obtained in step S2 to D50≤50μm by ball milling to obtain refined low-temperature carbonized material; S4, sand grinding modification: the refined low-temperature carbonized material obtained in step S3, nitric acid and deionized water are mixed, wherein H 2 O 2 The addition amount is 1% of the carbonized material, the solid content of the slurry is 25%, and the material is sand-ground to D50 = 7μm at a temperature of 50°C to obtain a surface-modified low-temperature carbonized slurry; S5, drying treatment: centrifuging, washing and drying the surface-modified low-temperature carbonized slurry obtained in step S4 to obtain a surface-modified low-temperature carbonized material; S6. High-temperature carbonization: The surface-modified low-temperature carbonized material obtained in step S5 is subjected to high-temperature carbonization under nitrogen gas protection, with a heating rate of 5°C / min, a carbonization temperature of 1400°C, and a carbonization time of 3h to obtain a surface-modified hard carbon material.
[0064] The electrochemical performance of the obtained material was tested according to the following method: the hard carbon material of application example 2, Super P, CMC, and SBR were mixed into a slurry in a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on a copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, with metallic sodium as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2032 type button battery in a glove box. The above button battery was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C-300 mAh / g) and a voltage range of 2-0.005V.
[0065] Comparative Example 1 This embodiment relates to a hard carbon negative electrode material for a sodium ion battery, and a preparation method thereof comprises the following steps: S1. Preparation of precursor: crush the coconut shell raw material, sieve it, and the sieve mesh size is 2 cm to obtain the precursor powder; S2, low temperature carbonization: the precursor powder obtained in step S1 is subjected to low temperature carbonization under nitrogen protection, wherein the heating rate is 5 °C / min, the treatment temperature is 600 °C, and the pretreatment time is 2 h. A low temperature carbonized material is obtained; S3, crushing and refining: crushing the low-temperature carbonized material obtained in step S2 to D50≤50μm by ball milling to obtain refined low-temperature carbonized material; S4, sand grinding modification: the refined low-temperature carbonized material obtained in step S3 is mixed with deionized water, the solid content of the slurry is 25%, and the material D50 is sand ground to 7 μm at a temperature of 50° C. to obtain a low-temperature carbonized slurry; S5, drying treatment: centrifuging, washing and drying the surface-modified low-temperature carbonized slurry obtained in step S4 to obtain a low-temperature carbonized material; S6. High-temperature carbonization: The low-temperature carbonized material obtained in step S5 is subjected to high-temperature carbonization under nitrogen gas protection, with a heating rate of 5°C / min, a carbonization temperature of 1400°C, and a carbonization time of 3h to obtain the hard carbon material of comparative example 1.
[0066] The electrochemical performance of the obtained material was tested according to the following method: the hard carbon material of comparative example 1, Super P, CMC, and SBR were mixed into a slurry in a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on the copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, with metallic sodium as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2032 type button battery in a glove box. The above button battery was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C-300 mAh / g) and a voltage range of 2-0.005 V.
[0067] Table 1 Test results of Application Example 1, Application Example 2 and Comparative Example 1 Figure 1 As shown: Table 1 Performance test results The constant current charge and discharge test measured that the reversible specific capacity of the hard carbon electrode in Application Example 1 was 306 mAh / g, and the first-week coulomb efficiency was 91.5%; the reversible specific capacity of the hard carbon electrode in Application Example 2 was 304 mAh / g, and the first-week coulomb efficiency was 91.3%; the reversible specific capacity of the hard carbon electrode in Comparative Example 1 was 301 mAh / g, and the first-week coulomb efficiency was 91.3%. By comparing Application Example 1, Application Example 2 and Comparative Example 1, the reversible capacity and first-week efficiency of the surface-modified hard carbon negative electrode material were not adversely affected.
[0068] In the sodium ion battery test, the capacity retention rates of Application Example 1, Application Example 2 and Comparative Example 2 at 2C current density were 73.5%, 72.4% and 61.3% respectively, indicating that the surface modification of the hard carbon material can effectively improve the rate performance of the hard carbon material. The reason is that the hard carbon surface modification layer increases the wettability of the hard carbon material surface with the electrolyte, increases the diffusion coefficient of sodium ions at the interface, and thus improves the rate performance of the material.
[0069] from Figure 1 It can be seen that in the sodium ion battery test, the capacity retention rates of Application Example 1, Application Example 2 and Comparative Example 2 after 200 cycles were 92.8%, 91.6% and 76.4%, respectively, indicating that the hard carbon surface modification layer can significantly improve the cycle performance of the hard carbon material. The reason is that the oxygen-containing functional groups on the surface of the hard carbon material can promote the decomposition of the electrolyte to build a thinner and more stable SEI, thereby improving the cycle stability of the hard carbon material. In addition, the better rate performance makes it difficult for the hard carbon negative electrode to precipitate sodium on the surface during charging, resulting in loss of active sodium and resulting in capacity decay.
[0070] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.
Claims
1. A method for preparing a surface-modified hard carbon sodium ion battery negative electrode material, characterized in that The following steps are involved: S1. Preparation of precursor: crushing and sieving the hard carbon raw material to obtain precursor powder; S2, low temperature carbonization: the precursor powder obtained in step S1 is subjected to low temperature carbonization under a protective atmosphere to obtain a low temperature carbonized material; S3, crushing and refining: crushing the low-temperature carbonized material obtained in step S2 to obtain refined low-temperature carbonized material; S4, sand grinding modification: wet sand grinding the refined low-temperature carbonized material obtained in step S3 with a modifier to obtain a surface-modified low-temperature carbonized slurry; S5, drying treatment: centrifuging, washing and drying the surface-modified low-temperature carbonized slurry obtained in step S4 to obtain a surface-modified low-temperature carbonized material; S6, high temperature carbonization: the surface-modified low-temperature carbonized material obtained in step S5 is subjected to high temperature carbonization under a protective atmosphere to obtain a surface-modified hard carbon material.
2. The method for preparing the surface modified hard carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step S3, the particle size of the refined low-temperature carbonized material is controlled to be: 10 μm ≤ D50 ≤ 200 μm.
3. The method for preparing the surface modified hard carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step S4, the modifier is an oxidant, and the oxidant is one or more of nitric acid and its salts, perchloric acid and its salts, dichromic acid and its salts, permanganic acid and its salts, persulfate and its salts, sulfuric acid and its salts.
4. The method for preparing the surface modified hard carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step S4, the amount of the modifier added is 0.1-5% of the mass of the refined low-temperature carbonized material, and the solid content is 10-50%.
5. The method for preparing the surface modified hard carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step S4, the particle size of the sanding process is controlled to be sanded until the material D50 is 3-8 μm.
6. The method for preparing the surface modified hard carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step S4, the temperature of the sanding process is controlled to be 30-80°C.
7. The method for preparing the surface modified hard carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step S2, the conditions for low-temperature calcination are: a heating rate of 2-15°C / min, a pretreatment temperature of 300-800°C, a pretreatment time of 1-5 h; and a protective atmosphere of nitrogen and / or argon.
8. The method for preparing the surface modified hard carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step S6, the high temperature carbonization conditions are: heating rate of 0.5-10°C / min, carbonization temperature of 900-1600°C, and carbonization time of 2-10 h.
9. The method for preparing the surface modified hard carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step S1, the hard carbon raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, and sub-bituminous coal; the sieve aperture is ≤2 cm.
10. The method for preparing the surface modified hard carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step S3, the pulverizing method is one or more of roller milling, mechanical milling, air flow milling, dry ball milling, and Raymond milling.
Citation Information
Patent Citations
Direction control method of surface oxygen functional groups on coal-based hard carbon for sodium-storing cathodes
CN109796003A
Biomass-based sodium ion battery hard carbon anode material, and preparation method and application thereof
CN110719891A
Biomass-based functional group modified sodium ion battery anode material, preparation method and application thereof
CN110753673A
Coal-based hard carbon material, preparation method thereof and application of coal-based hard carbon material as sodium-ion battery negative electrode material
CN118545698A
